Graphene nanomesh and polymeric material at cutting edge. Issue 8 (24th May 2019) - Kausar, Ayesha
ABSTRACT: Graphene nanomesh (GNM) is a nanostructure of graphene having periodic nanoscale holes. GNM has attracted extensive interest owing to promising chemical, thermal, electronic, photonic, and other vital characteristics. This review merely covers significant facts regarding structure, properties, and graphene patterning techniques to form nanomesh. Polymeric scaffolding has been used as one of fabrication techniques. Among few polymers used in polymer/GNM nanomaterial comprise polyaniline, poly(methyl methacrylate), poly(vinylidene fluoride), polystyrene, and polyethylene, as deliberated in this article. Recently, extensive investigations have been carried out on potential relevance of polymer/GNM nanomaterial in supercapacitor, sensor, Li–ion batteries, organic photovoltaic, and electronic nose. Graphical Abstract: